Intergenerational mobility and the rise and fall of inequality: Lessons from Latin America - Guido Neidhöfer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
Countries with high income inequality also show a strong association between parents' and children's economic well-being; i.e. low intergenerational mobility. This study is the first to test this relationship in a between-country and within-country setup; using harmonized micro data from 18 Latin American countries, spanning multiple cohorts. It is shown that experiencing higher income inequality in childhood is associated with lower intergenerational mobility measured in adulthood. Following the same methodology, the influence of economic growth and public education is evaluated: both are positively, significantly, and substantially associated with intergenerational mobility.
Keywords: D63; I24; J62; O15; 330; Inequality; Intergenerational Mobility; Equality of Opportunity; Human Capital; Growth; Development; Public Education; Great Gatsby Curve; Latin America